An Analysis of Techniques and Challenges in Teaching Pronunciation to Young Learners: A Case Study at A Primary School Level - Yolinda Pramudanti; Seful Bahri (Universitas Negeri Semarang, 2026)
Pronunciation plays a crucial role in communication, especially for early English learners during their optimal language-acquisition period. However, many primary school teachers struggle with effective pronunciation instruction due to limited training and resources. This research aimed to identify the methods teachers employed, the obstacles they encountered, and how students responded to pronunciation instruction. This study investigates the techniques used and challenges faced by teachers in teaching pronunciation to young learners at one of the primary schools in Pati, Central Java, Indonesia. Using a descriptive qualitative approach, data were collected through classroom observations, interviews with one teacher and six students, and document analysis. The findings revealed that drilling and repetition were the most commonly used techniques, although students perceived them as monotonous. More engaging strategies, such as using games and audiovisual media, increased student motivation and participation more effectively. Challenges included a lack of appropriate materials, limited technological tools, and the influence of students' first language. This study concludes that while traditional methods remain dominant, integrating interactive, technology-supported techniques can enhance the effectiveness of pronunciation instruction. The results suggest more targeted teacher training and resource development to support pronunciation teaching at the elementary level.